Pengaruh Return On Equity Dan Debt To Equity Ratio Terhadap Return Saham Pada Pt. Astra International, Tbk. - Sari, Suci Indah; Yasin, Nurfatwa Andriani (LPPM STIE Tri Dharma Nusantara - Makassar, 2024)
The purpose of this study is to determine the effect of Return On Equity and Debt to Equity Ratio on Stock Return at PT. Astra International, Tbk. The type of data used in this study is quantitative data, the source of data used is secondary data. The analysis methods used are descriptive analysis methods and multiple linear regression, determination coefficient, correlation coefficient, t test, and f test. The results of the regression equation Y = -14.765 + 0.576X1 – 0.093X2 + e. Simultaneously it does not have a significant effect on the variables Return On Equity and Debt to Equity Ratio to Return Shares at PT. Astra International, Tbk. Return On Equity positively does not have a significant effect on Share Return at PT. Astra International, Tbk. Debt to Equity Ratio does not affect Share Return at PT. Astra International, Tbk.